Nonablative fractional laser therapy for treatment of actinic keratosis with 3‐months follow‐up. (1st March 2020) - Nourmohammad Pour, Pedram; Esmaili, Nafise; Ehsani, Amirhooshang; Hamzelou, Shahin; Nasimi, Maryam
Abstract: Background: Actinic keratosis (AK) is a common skin disorder that is treated with different treatment modalities. Aims: The aim of this study was to assess the therapeutic effect of a 1540‐nm nonablative fractional laser on the AK. Methods: Ten patients with 31 AK were included in the study according to the inclusion and exclusion criteria. Treatment with nonablative fractional laser (1540 nm) 3 times at 4 weeks intervals in a noncontact mode was applied. Clinical severity was assessed at each session and 3 months after the last session. It is pertinent to mention that the patients were also involved in the assessment of improvement. Results: The results of present study showed that in comparison to the baseline, 3‐session AK therapy with nonablative fractional laser significantly not only improved the AK severity by 79%, but also reduced the AK counts (from 31 to 17). On the other hand, the patients consented to the therapeutic effect. Conclusion: According to the obtained results and available studies, it seems that therapy with a 1540‐nm nonablative fractional laser could be considered as a safe and effective alternative therapeutic option for the treatment of AK.